Pamilyang pinoy, ano ka ngayon? a comparative content analysis of parents and chic in its portrayal of Filipino family - Abarabar, Blanche Y.
This research, entitles Pamilyang Pinoy, Ano ka na ngayon? : A Comparative Content Analysis of Parents and Chic in its Portrayal of Filipino Family, is a descriptive study. The main problem of this study dealt on the portrayal of family-oriented magazines. It generally tries to determine how Parents and Chic portrayed Filipino family. Its specific objectives are to determine the Filipino values, family issues, treatment and the photographs/illustrations attached to the feature articles of Parents and Chic and compare the two family-oriented magazines. The study used the random sampling method. A total of 100 feature articles were drawn and analyzed from issues of Parents and Chic published in the period of January to December 1998. Results of the study showed that the magazines, Parents and Chic, portrayed the Filipino family positively. The top five Filipino values projected in both magazines were family orientation, respect for women, Godly (maka-Diyos), concern for others (pakikipagkapwa-tao) and joy and humor. It was found out that majority of the feature articles in both magazine tackled parenthood. This family discussed the role of parents, the maternal and childcare, child rearing, adolescence stage, parents and child relationships and sibling relationships. However, the two magazines varied when it came to their second and third frequently projected Filipino value and prioritized family issue. Parents focused more on family structure and functions and husband and wife roles. Meanwhile, Chic emphasized the issue on love, sex and marriage and the family structure and functions. Furthermore, the feature articles of the two magazines were accompanied with photographs and illustrations. It was seen that the type of photographs/illustrations shown in the feature articles of both magazines was different. Parents presented the article with photograph/illustrations mostly of family. On the other hand, Chic presented it with photographs/illustrations of couple/husband and wife/man and woman. The researcher concluded that these family-oriented magazines portrayed Filipino family positively. However, the two magazines were different in terms of its attention on Filipino values, emphasis of certain family issue, treatment on the feature articles and the choice of photographs/illustrations. The researcher recommended that future studies be made in determining the perception of readers of these family-oriented magazines on Filipino family. Also, a historical study should also be considered in order to describe the influence of management on the content of the magazines.